2019
DOI: 10.3847/2041-8213/ab4424
|View full text |Cite
|
Sign up to set email alerts
|

New Candidate Planetary Nebulae in Galactic Globular Clusters from the VVV Survey*

Abstract: Only four globular cluster planetary nebulae (GCPN) are known so far in the Milky Way. About 50 new globular clusters have been recently discovered towards the Galactic bulge. We present a search for planetary nebulae within 3 arcmin of the new globular clusters, revealing the identification of new candidate GCPN. These possible associations are PN SB 2 with the GC Minni 06, PN G354.9-02.8 with the GC Minni 11, PN G356.8-03.6 with the GC Minni 28, and PN Pe 2-11 with the GC Minni 31. We discard PN H 2-14 locat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…We note that VVV-CL160 is also interesting because there are three candidate planetary nebulae (PNe) in the vicinity: the closest one is PHR J1806−1956 at 4.6 north of the GC center; then there are PN PM 1−209 and IRAS 18036−1954 at 4.9 west and 5.2 northwest from the center, respectively. Their membership in the GC is unknown; determining this membership spectroscopically would be significant as there are a very limited number of GC PNe known in our Galaxy (Minniti et al 2019). Of these three PNe, as far as we know only IRAS 18036−1954 has an estimated distance measurement, D = 1.67 kpc (Ortiz 2013), that is smaller than our distance determination for VVV-CL160.…”
Section: Confirmation Of a New Globular Clustermentioning
confidence: 62%
“…We note that VVV-CL160 is also interesting because there are three candidate planetary nebulae (PNe) in the vicinity: the closest one is PHR J1806−1956 at 4.6 north of the GC center; then there are PN PM 1−209 and IRAS 18036−1954 at 4.9 west and 5.2 northwest from the center, respectively. Their membership in the GC is unknown; determining this membership spectroscopically would be significant as there are a very limited number of GC PNe known in our Galaxy (Minniti et al 2019). Of these three PNe, as far as we know only IRAS 18036−1954 has an estimated distance measurement, D = 1.67 kpc (Ortiz 2013), that is smaller than our distance determination for VVV-CL160.…”
Section: Confirmation Of a New Globular Clustermentioning
confidence: 62%
“…The Milky Way contains around 160 known GCs, although Minniti et al (2019) have reported an additional 50 GC candidates in the direction of the Milky Way's bulge. The recent compilation of K19 lists 96 GCs with ages and metallicities taken from three large studies.…”
Section: The Milky Way Gc Systemmentioning
confidence: 99%
“…At the other extreme, if we scale the expected number from the stellar halo in Moe & De Marco (2006), the number of PNe decreases by a factor of ∼ 10 2 due to older ages of the system (a relatively shorter dissipation timescale of stellar envelopes), but this estimate is quite uncertain. On the observational ground, however, there are 8 PNe known in the Galactic globular clusters (Jacoby et al 1997;Minniti et al 2019), from which one can naively expect ∼ 10 3 PNe since the nuclear bulge is ∼ 100 times more massive than the entire globular cluster system in the Milky Way.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…On the other hand, if the observed lack of PNe is rooted in astrophysical origins, this may indicate that the PN formation channel such as binary interactions (e.g., Minniti et al 2019) is overpowered by suppression mechanisms that can reduce the envelope mass of asymptotic giant branch (AGB) stars. Some stars can also skip the AGB phase and directly evolve into hot subdwarfs, if the envelope mass is not high enough.…”
Section: Discussion and Summarymentioning
confidence: 99%